Pengembangan Karir Guru dan Tenaga Kependidikan di SMP Negeri 5 Cimahi - Ahmad, Syatiri; Septiyani, Tentri (Universitas Pendidikan Indonesia, 2023)
Human resource management (HRM) is an important thing in the implementation of education. Education can be said to be of quality or quality with support from human resources. Therefore, every educational institution must pay attention to human resources and manage them well, in order to create high-quality education. Therefore, research was conducted at Junior High School 5 Cimahi to find out the extent of HRM being carried out at the school in order to see the quality and quality of the HR empowerment being carried out. Data collection techniques were carried out by direct interviews with the school principal. Career development in human resource management at Junior High School 5 Cimahi is structured and implemented in accordance with the needs of each human resource in the school. Career development of an educator is very influential in increasing professionalism as an educator and education staff